Prevalence and Vulnerability to Drug Abuse among Students of High School and Colleges in Riyadh, Saudi Arabia: Cross-Sectional Study - Khader, Pharm. D, BCPS, Khadeejeh; Mohamed, Pharm. D., Alaa; Almesned, Pharm. D., Nahla; Alrukiti, Pharm. D., Nourah; Zayed, Pharm. D., Alaa; Alghamdi, Pharm. D., Beshaier; Al Shehri, Pharm. D., Hind (International Journal of Innovative Research in Medical Science, 2019)
Background: Drug and substance abuse is a significant burden worldwide. This problem affects many families in each community in a way or another. By the end, the misuse of these substances can lead to health associated problems in addition to social, economic, and legal issues. The Students’ susceptibility to drug abuse depends on different factors such as low self-esteem or to gain acceptance. Objectives: To compare the attitude of drug abuse between high school students and college students and to assess the common reasons that led to increase number of abusers. Methods: The study was conducted between February and May 2018 in Riyadh city on colleges and high schools students. A sample of 935 students aged between 15 and 25 years were randomly selected by distributing an online self-administered questionnaire for data collection. Results: The overall prevalence of drug abuse in Riyadh city was 18.94% among high school students (8.07% and 10.87% female abusers) and 24.14% among college students (13.87% male and 10.28% female abusers). A significant relationship was found between abuse and being a male students in college. The prevalence was different for high schools, the most widely abused substance was alcohol (44.5%) followed by Hashish (40.19%). These were used for different reasons the most common was for fun followed by escaping from problems. Conclusion: The study demonstrated that college students have higher prevalence and vulnerability to drug abuse than high school students, with the most commonly used substances being Alcohol and Hashish. According to our findings, the main reasons behind students’ abuse of drugs are due to boredom thus wanting to have fun and having problems so they escape from them by drugs. Due to the prevalence of drug abuse and the various reasons behind it as demonstrated in our study, we believe that parents should be more involved with their children’s lives, students should be encouraged to have hobbies in their spare time and guidance should be provided for them in order to learn how to deal with their problems correctly.